Nasopharyngeal pneumococcal carriage among unvaccinated healthy Sri Lankan children during the COVID-19 pandemic - Gonapaladeniya, Madhusha; Liyanage, Guwani; Weerasekera, Manjula; Perera, Roshan; Dissanayake, Thushari (The Journal of Infection in Developing Countries, 2026)
Introduction: Streptococcus pneumoniae is a major cause of morbidity and mortality worldwide, especially in children. This study focused on the prevalence, serotypes, antibiotic resistance, and biofilm formation of pneumococci colonising an unvaccinated Sri Lankan children cohort aged ≤ 2 years during the COVID-19 pandemic. Methodology: This descriptive, cross-sectional study was carried out between April to August 2021 among healthy children visiting routine immunisation clinics in the Colombo district, Sri Lanka. Nasopharyngeal swabs (NPS) from healthy children were collected and cultured on sheep blood agar to isolate S. pneumoniae and confirmed by lytA gene-specific PCR. All confirmed S. pneumoniae isolates underwent capsular sequence typing to detect serotypes. Antibiotic susceptibility was determined. In-vitro biofilm-forming ability was assessed using the crystal violet assay, tetrazolium reduction assay, and scanning electron microscopy. Results: The S. pneumoniae colonization rate of healthy children was 5.7% (20/350). Serotype 19F was the commonest, and 80% (16/20) of isolates were covered by the 13-valent pneumococcal conjugate vaccine (PCV13). All isolates were sensitive to levofloxacin, vancomycin, and linezolid but showed significant non-susceptibility to penicillin (70%, 14/20) and cefotaxime (15%, 3/20) at non-meningitis break points. All isolates formed biofilms. Conclusions: A comparatively lower rate of pneumococcal colonisation was observed among this cohort compared to the current literature. The most prevalent serotype identified was 19F. Serotype pattern was similar to the pre-vaccine era pattern reported globally. Antibiotic non-susceptibility rates were high for penicillin and erythromycin. Almost all isolates showed evidence of in vitro biofilm formation.